Evaluasi Komparatif Penggunaan Tepung Cacing dan Tepung Ikan sebagai Sumber Bahan Baku Protein Pakan terhadap Performa Pertumbuhan Ikan Lele - Masriah, Andi; Pratiwi, Rizky Kusma; Nadiro, Vina Nur; Cahya, Muhamad Dwi; Hariyono, Nidya Aufa Rosie; Safira, Bela; Khairunnisa, Easty; Badzlin, Shierleen Zahra (Journal Galung Tropika, 2025)
Fishmeal is the primary raw material in fish feed formulations as a source of protein raw materials. Its limited availability and fluctuating prices encourage using alternative protein sources, one of which is worm meal. This study compare the use of fish meal and worm meal in catfish (Clarias sp.) feed the hepatosomatic index (HSI), blood glucose levels, and gastric emptying rate. The research was conducted using an experimental method with two treatments: fishmeal-based and worm meal-based. HSI data obtained were analyzed by independent-sample T-test analysis, while data on blood glucose levels and gastric emptying rate were analyzed descriptively. The results showed no significant difference (p>0.05) between treatments on hepatosomatic index. Fluctuations in blood glucose levels are also in line with the rate of gastric emptying, which is not too different between treatments. This study showed that worm meal has the potential to be used as an alternative to fish meal in catfish feed without causing physiological changes.